Coexistence of Hodgkin's Lymphoma and Castleman's Disease: A Case Report with Successful Response to Chemotherapy and Radiotherapy. (5th December 2013) - Mohtaram, Amina; Afif, Mohammed; Sghiri, Tanae; Rami, Amal; Latib, Rachida; Kettani, Fouad; Ben Ameur El Youbi, Meryam; Boutayeb, Saber; Kebdani, Tayeb; Benjaafar, Noureddine; Aaribi, Imane; Errihani, Hassan
Abstract : Background . Castleman's disease is a rare clinicopathological entity of unknown origin. Coexistence of Hodgkin's lymphoma and Castleman's disease is rare. We report a case of Hodgkin's disease of cervical lymph nodes in a patient previously diagnosed with Castleman's disease. Case Presentation . A 43-year-old man admitted in July 2009 for a right cervical pain with lymph node at the physician examination. He underwent a right adenectomy and histological studies showed typical features of Castleman's disease. Three years after, the patient consulted for increasing the volume of cervical lymph node. Clinical examination showed a right cervical lymph node of 3 cm. The computed tomography scan of chest, abdominal and pelvic was normal. Histological and immunohistochemical studies of cervical lymph node biopsy specimen were in favor of Castleman's disease associated with Hodgkin's disease. Reed-Sternberg cells were positive for CD15 and CD30. The patient received chemotherapy based on anthracyclines, bleomycin, vinblastine, and dacarbazine (ABVD) and radiotherapy with complete response. Conclusion . Prevalence of Hodgkin's lymphoma in Castleman's disease is more difficult to establish because of the low number of cases reported in the literature.